Reverse Orientation of Aldehyde Dehydrogenase (ALSH) Gene Under TA29 Promoter in Tobacco Plants (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Tobacco; TA29 promoter; aldehyde dehydrogenase gene Bangladesh j. genet. biotechnol. 7(1&2): 57-60 2006 (June & December)